Verified Time. - Stavrou, Angelos; Voas, Jeffrey (Computer (00189162), 2017)
A provably secure timestamping system could be achieved by combining the trustworthiness and accuracy that comes from having a set of trusted centralized timestamping authorities with the open, decentralized nature of blockchain protocols.